The Role of Supply Chain Integration on Green Practices and Performance in a Supply Chain Context. A Conceptual Approach to Future Research - Veera Pandiyan Kaliani Sundram; Premkumar Rajagopal; Atika Shamsul Bahrin; Geetha Subramaniam (International Journal of Supply Chain Management, 2018)
The purpose of this paper is to investigate the current research relationship between green supply chain management practices, supply chain integration and the manufacturing firms performances in Malaysia. Also, to improves the conceptual knowledge by compare and contrast the relationship between each dimension. The study thoroughly analyzes, reviews and explains each dimension in detail and their relationships from various previous literature perspectives. The paper is one of the first to identify and discuss conceptually the use of green supply chain management practices and supply chain integration in measuring the manufacturing performance in a single setting in a developing country.